2016
DOI: 10.1016/j.npbr.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neural differentiation maturity status of human induced pluripotent stem cells prior to grafting in a subcortical ischemic stroke model

Abstract: Neural cell grafting is a promising therapy for stroke, but the optimal differentiation status of the cells prior to grafting is unclear. We grafted cells at different maturity stages (days 28, 42, or 56 of in vitro neural differentiation) into the brains of eight-week-old rats one week after subcortical ischemic stroke, and assessed motor and sensory behavioral recovery over one month. We did not find a difference between the grafted or control groups on behavioral recovery, or on brain tissue outcomes includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thus, the carrier and cell maturity are important for brain tissue recovery. Others similarly found no difference in cell survival depending on maturity [95,96]. However, Fig.…”
Section: Key Scaffold Properties For Brain Tissue Regenerationmentioning
confidence: 70%
“…Thus, the carrier and cell maturity are important for brain tissue recovery. Others similarly found no difference in cell survival depending on maturity [95,96]. However, Fig.…”
Section: Key Scaffold Properties For Brain Tissue Regenerationmentioning
confidence: 70%
“…Recent studies have focused on expanding applications of iPSCs in animal models of aging [130], and tried to determine the optimal timing for transplantation in terms of differentiation states [131,132] and the effect of pathological conditions on transplanted cell viability and differentiation [133]. These studies showed that iPSC-derived cells were also effective in reducing the damage caused by aging or reactive gliosis, and completely differentiated cells could result in decreased viability after transplantation.…”
Section: Applying Induced Pluripotent Stem Cells In Animal Models Of mentioning
confidence: 99%
“…8-week old rats received intracerebral cell grafts at four different time points. The authors reported no significant difference among iPSCs at days 7, 28, 42, and 56 on the infarct size, behavioral recovery, microgliosis, astrocytosis, or neurologic outcome [ 60 ].…”
Section: Inducible Pluripotent Stem Cellsmentioning
confidence: 99%